Complete Sequence and Characterization of Mitochondrial and Chloroplast Genome of Navicula incerta CACC 0356 - Zhaokai Wang; Xiaoyu Wei (Life)
Navicula incerta, a marine benthic diatom, holds promise for human nutrition and health as well as for aquaculture applications. However, the scarcity of organelle genome data within the Navicula clade has impeded a comprehensive understanding and utilization of this group. Our research presents a pioneering exploration into the complete mitochondrial and chloroplast genome sequences of N. incerta CACC 0356, shedding light on its phylogeny and evolutionary history. The mitochondrial genome (mtDNA) spans 61,320 bp with a GC content of 29.87%, comprising one circular DNA molecule that encodes for 34 protein-coding genes, 24 tRNAs, and 34 rRNAs. Whereas, the chloroplast genome (cpDNA) is larger at 129,090 bp, encompassing 127 protein-coding genes, 30 tRNAs, and 7 rRNAs. Notably, the cpDNA of N. incerta is approximately 2.1 times the size of its mtDNA. Our annotation identified four genes that are partially situated in the homologous regions between the mitogenome and chloroplast genome, totaling 372 bp, which represents 0.61% of the entire mitogenome. Comparative analyses revealed that N. incerta CACC 0356 is closely affiliated with Fistulifera saprophila and Fistulifera solaris, both members of the Naviculaceae order. This study significantly expands the mitochondrial and chloroplast genomic resources for algae and lays a foundation for the development of genetic diversity analyses in algae.